Comparative study on the adsorption of heavy metal ions by kaolin, sand, activated carbon and their admixtures - Tan Wei Hsiang (2022)
Heavy metals contaminant has been widely spread to the environment. Soils have been noted as a source for heavy metals accumulation or released to the environment. Adsorption was found to be the most important process that responsible for accumulation of heavy metals in soils. This study evaluates the adsorption of selected heavy metals cu2+, Pb2+ and zn2+ onto the adsorbents that are clay, sand, activated carbon, field soil and their mixture composition for the purposes to determine their adsorption isotherms in competitive and noncompetitive system. Physiochemical properties of adsorbents were characterized by BET, pycnometer, particles size analyzer, XRD and XRF. Langmuir Isotherm Model based on Pseudo Ideal Monolayer Theory and directly interpreted from excess adsorption isotherm and also Freundlich Model were the adsorption isotherm applied in this present work. The experimental data are well fitted with Langmuir Isotherm Model based on Pseudo Ideal Monolayer Theory and directly interpreted from excess adsorption isotherm with the significant correlation coefficient R2 (above 0.85). However, the value of Pseudo Ideal Monolayer Theory adsorption capacity (xl0·7mg/g) is small in comparison with directly interpreted from excess adsorption isotherm (x10·3mg/g) due to in Pseudo Ideal Monolayer model, all aqueous speciation was accounted in analysis adsorption isotherm which is totally different from the past research. This study reveals that the mixture of composition contains more clay and activated carbon, respectively increases the adsorption capacity. Eg., clay and sand at ratio 50%:50% to 90%: 10%, the adsorption capacity towards Cu2+ increase from 0.727mg/g to 2.042mg/g; activated carbon and clay at ratio 10%:90% to 70%:30%, the adsorption capacity towards Cu2+ increase from 2.324mg/g to 4.227mg/g. High cation exchange capacity and surface area in activated carbon (90cmol/kg, 621.86m2/g) possesses higher adsorption capacity than clay (13.75cmol/kg, 16.59m2/g) and sand (0.21cmol/kg, 0.57m2/g). The descending adsorption capacities of adsorbents in this study are as the following: activated carbon>clay>sand. The adsorption capacity of field soil toward Cu2+ (5.953xl0·4mg/g) was more than four times higher than the field soil without organic matter (1.438xl0·4mg/g). The adsorption capacities of adsorbents in noncompetitive adsorption also found to be higher than the competitive adsorption due to the number of adsorption sites are fixed on the surface of adsorbent whereas heavy metal ions needed to compete in adsorbing onto the adsorption sites. Overall, the adsorption capacity in all types of adsorbents show the same pattern of heavy metals adsorption with Pb2+>cu2+>zn2+. The selectivity of adsorbents toward Pb2+ ions is higher than Cu2+ and Zn2+ as it is influence by the first hydrolysis constant, ionic radius and hydration energy value of heavy metal. The comparison of application on linear and non-linear regression indicates the nonlinear regression method providing much more consistent and reliable results (overall correlation coefficients R2 are above 0.9). In dynamic simulation of adsorption, the presence of clay in the mixed composition of clay and sand proportionally enhances the breakthrough time of Pb2+, Cu2+ and zn2+ The presence of organic matter in soil was also indicates that the adsorption capacity of soil increases by prolonging the breakthrough time of heavy metal. Similarly, in the binary competitive and ternary competitive heavy metal transport, Pb2+ shows strong adsorbate characteristics onto clay and sand compared with cu2+ and zn2+. Therefore, it is suggested this simulation should be extended to type of soil components which is very close or matching to the real soil texture and composition.